The Effect of Operating Cash Flow, Total Asset Turnover, and Inflation on Stock Return in Indonesian Consumer Goods Firms - Assyifa Khaira Yahya; Ali Riza Fahlevi (Academic Bright Collaboration, 2026)
Purpose – The study aimed to assess the impact of operating cash flow ratio, total asset turnover, and the inflation rate on the stock return behavior of consumer goods firms on the Indonesia Stock Exchange between 2020 and 2024. The outlined years indicate distinct phases in the economy, from the ruptures of the COVID-19 to the periods of post-containment recovery, inflation, and the evolving patterns in the realm of consumer spending. Such evidence supports analysis of company financial performance and the capital market economic behavior.Methods – For this study, panel data regression analysis was used. The financial data were from annual financial statements, and the macroeconomic data were from the years 2020 to 2024. Purposeful sampling resulted in a study sample of 30 companies, yielding 150 data observations. These data were initially subjected to analysis using descriptive statistics. Having satisfied the classical assumption tests and run through the model selection procedures, the analysis settled on FEM as the most suitable model.Findings - This study also found that stock returns were greater for companies that had a greater operating cash flow. Total asset turnover and the inflation rate did not have a significant effect on stock returns, but the three variables did have a significant effect when considered together. This implies that when an investor is in need of liquidity and examines a company's cash flow, he/she will focus to a greater extent on the operating cash flow, rather than the asset-utilization efficiency and the inflation of the country.Research implications – These results provide company managers and investors with a more descriptive representation of the importance of operating cash flow in making operating and financial investments. Due to the variables and estimation methods applied, the researchers expect that future studies will improve on the gaps created in this estimation.Originality – The study's originality is in the combined effect of operating cash flow, total asset turnover, and inflation on stock returns in the consumer goods sector, using the panel data regression approach. The results were in accordance with the signaling theory, which provides that the operating cash flow that is released is good news to potential investors, because of the positive operating and financial concerns of the company.